Pharmacological Activities of Ginkgolic Acids in Relation to Autophagy - Yuan Ding; Zheheng Ding; Jin Xu; Yueying Li; Min Chen (MDPI AG, 2022)
Plant-derived natural compounds are widely used as alternative medicine in healthcare throughout the world. Ginkgolic acids, the phenolic compounds isolated from the leaves and seeds of Ginkgo biloba, are among the chemicals that have been explored the most. Ginkgolic acids exhibit cytotoxic activity against a vast number of human cancers in various preclinical models in vitro and in vivo. Additionally, the pharmacological activities of ginkgolic acids are also involved in antidiabetic, anti-bacteria, anti-virus, anti-fibrosis, and reno/neuroprotection. Autophagy as a highly conserved self-cleaning process that plays a crucial role in maintaining cellular and tissue homeostasis and has been proven to serve as a protective mechanism in the pathogenesis of many diseases, including neurodegenerative diseases, cancer, and infectious diseases. In this review, we surveyed the pharmacological activities of the major three forms of ginkgolic acids (C13:0, C15:1, and C17:1) that are linked to autophagic activity and the mechanisms to which these compounds may participate. A growing body of studies in last decade suggests that ginkgolic acids may represent promising chemical compounds in future drug development and an alternative remedy in humans.